Electrochemical sensor for detecting 5-hydroxytryptamine

By using a composite material of two-dimensional layered transition metal carbide, nitrogen-doped graphene and platinum nanoparticles in the electrochemical sensor to modify the electrodes and perform molecular imprinting polymer modification, the problem of poor film formation ability of MXene material is solved, and efficient detection of serotonin is achieved.

CN119534566APending Publication Date: 2025-02-28LANZHOU FOCI PHARM CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411449815.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When using MXene material alone as the sensing layer, the interaction between the van der Waals force and hydrogen bonds between the two-dimensional layers leads to poor stacking and film formation capabilities, reducing the ion adsorption sites and reactive sites of the material, thereby affecting electron transport.

Method used

The electrode was modified using a composite material composed of two-dimensional layered transition metal carbides, nitrogen-doped graphene and platinum nanoparticles, and a molecularly imprinted polymer with serotonin as the template molecule was modified to form a MIP/Pt@MXene-NG/SPCE electrochemical sensor.

Benefits of technology

By improving the film-forming ability and electron transport characteristics of MXene, the detection sensitivity and selectivity of electrochemical sensors are significantly improved, and efficient detection of serotonin is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534566A_ABST
    Figure CN119534566A_ABST
Patent Text Reader

Abstract

The electrochemical sensor for detecting 5-hydroxytryptamine comprises an electrode, and is characterized in that the surface of the electrode is sequentially modified with (a) a composite material composed of two-dimensional layered transition metal carbide, nitrogen-doped graphene and platinum nanoparticles; and (b) a molecularly imprinted polymer taking 5-hydroxytryptamine as a template molecule. Compared with the prior art, the electrochemical sensor disclosed by the invention has good selectivity, stability and sensitivity on 5-hydroxytryptamine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical sensors, and in particular relates to an electrochemical sensor for detecting 5-hydroxytryptamine. Background Art

[0002] Depression is a common affective disorder that seriously threatens human physical and mental health. The decrease in the level of monoamine neurotransmitters such as 5-hydroxytryptamine (5-HT) in the synaptic cleft is an important mechanism for the occurrence of depression. As a monoamine neurotransmitter, 5-HT is closely related to the occurrence and development of depression and can be used as a marker for the diagnosis of depression. Measuring the level of 5-HT can help diagnose depression; on the other hand, some antidepressants such as fluoxetine treat depression by regulating the level of 5-HT. By detecting the patient's 5-HT level, it can provide a basis for the precise treatment of antidepressants.

[0003] The chemical formula of two-dimensional layered transition metal carbides and nitrides (MXene) is M n+1 X n T x , where M represents a transition metal (Ti, V, Nb, Ta, Cr, Mo, etc.), X represents carbon and / or nitrogen, Tx represents a hydrophilic surface functional group, such as O, −OH or −F, and n=1~3. Because of its large number of active groups, high chemical catalytic ability, large specific surface area, high conductivity, etc., it can provide abundant contact sites and improve the electron transfer rate, and has been widely used in catalysis, electrochemical sensing, energy storage and other fields. However, when MXene materials are used alone as sensing layers, the interaction between the two-dimensional interlayer van der Waals force and hydrogen bonding causes MXene to accumulate and have poor film-forming ability, reducing the material's ion adsorption sites and reactive sites, making the material's electron transfer more challenging. Summary of the invention

[0004] Based on the above-mentioned prior art, the object of the present invention is to provide a MXene-based electrochemical sensor for detecting 5-hydroxytryptamine.

[0005] To achieve the above object, the present invention adopts the following technical solution: An electrochemical sensor for detecting 5-hydroxytryptamine, the electrochemical sensor comprising an electrode, the surface of the electrode being modified in sequence with: (a) Composite materials consisting of two-dimensional layered transition metal carbides, nitrogen-doped graphene, and platinum nanoparticles. (b) Molecularly imprinted polymer with 5-HT as the template molecule.

[0006] Preferably, the electrode is a carbon electrode.

[0007] More preferably, the electrode is a screen-printed carbon electrode.

[0008] Preferably, the two-dimensional layered transition metal carbide is two-dimensional layered Ti3C2.

[0009] Preferably, the mass ratio of the two-dimensional layered transition metal carbide to nitrogen-doped graphene is 3:1 to 1:2, more preferably 2:1.

[0010] Preferably, the ratio of the total mass of the two-dimensional layered transition metal carbide and the nitrogen-doped graphene to the mass of the platinum nanoparticles is 5:1 to 1:1, more preferably 3:1.

[0011] Preferably, the composite material is prepared by the following steps: The two-dimensional layered transition metal carbide and nitrogen-doped graphene are mixed in a water solvent and separated to obtain MXene-NG; The composite material is obtained by mixing MXene-NG and chloroplatinic acid in a water solvent, and then adding a reducing agent to reduce the chloroplatinic acid.

[0012] Preferably, the modification amount of the composite material on the electrode surface is 20-50 μg.

[0013] Preferably, the monomer of the molecular imprinting polymer is o-phenylenediamine.

[0014] Preferably, the molecular imprinting polymer is modified on the electrode surface by electropolymerization.

[0015] Preferably, the electropolymerization method comprises the following steps: (1) placing the electrode modified with the composite material in a solution containing template molecules and polymer monomers, and performing cyclic voltammetry scanning; (2) After scanning, the template molecules are eluted.

[0016] Preferably, in step (1), the potential range of the cyclic voltammetry scan is: 0~0.8 V, the scan rate is: 0.1 V / s, and the number of scans is 15~30.

[0017] Preferably, step (2) adopts constant potential elution, and the eluent is a hydrochloric acid solution. More preferably, the potential during elution is -0.4 V.

[0018] Preferably, the molar ratio of the template molecule to the polymer monomer is 1:5-1:11, more preferably, the molar ratio of the template molecule to the polymer monomer is 1:7, and the concentration of the polymer monomer is 7 mmol / L.

[0019] A method for detecting serotonin, comprising: (1) incubating the electrochemical sensor according to claim 1 in a 5-hydroxytryptamine sample solution for a certain period of time; (2) The DPV method was used to measure the electrochemical sensor before and after incubation to obtain the current response difference before and after incubation.

[0020] Preferably, an electrolyte containing K3[Fe(CN)6] / K4[Fe(CN)6] is used as the electrolyte for DPV measurement. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD spectra of MXene (A) and infrared spectra of MXene, NG, MXene-NG and Pt@MXene-NG (B).

[0022] Figure 2 Scanning electron microscope images of MXene, MXene-NG, Pt@MXene-NG, NIP / Pt@MXene-NG and MIP / Pt@MXene-NG.

[0023] Figure 3 DPV curves (A) and EIS curves (B) of SPCE, MXene / SPCE, MXene-NG / SPCE and Pt@MXene-NG / SPCE.

[0024] Figure 4 CV curves of Pt@MXene-NG / SPCE at different scanning speeds (A) and the linear fitting diagram of peak current and scanning speed (B).

[0025] Figure 5 DPV curves of MIP / Pt@MXene-NG / SPCE after incubation in 5-HT solutions with different concentrations (A) and the linear fitting diagram of the current response difference and 5-HT concentration (B).

[0026] Figure 6 Selectivity (A) and stability (B) of MIP / Pt@MXene-NG / SPCE detection.

[0027] Figure 7 Schematic diagram of the structure of the microfluidic chip.

[0028] Figure 8 A cross-sectional view of the microfluidic chip.

[0029] Fig. 9 is the DPV response current of the electrodes prepared under different conditions. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described in detail below in conjunction with embodiments.

[0031] Ti3C2T x MXene (two-dimensional layered Ti3C2) is prepared by the traditional hydrofluoric acid etching method (see: ACSApplied Materials&Interfaces, 14 (2022) 16300-16309; Nature, 516 (2014)78-81). The specific operation is as follows: First, 1 g of LiF (lithium fluoride) was added to 12 mL of 9 M HCl to obtain an HF solution; then 1 g of Ti3AlC2 powder was added to the above solution and reacted at 45°C with magnetic stirring for 30 h; finally, the reaction mixture was centrifuged at 3500 rpm for 10 min, washed with deionized water until the supernatant was approximately neutral, and the obtained suspension was ultrasonically treated for 30 min, centrifuged at 3500 rpm for 60 min, and the upper dark green suspension was collected and freeze-dried to obtain MXene. Figure 1 The XRD characterization results of (A) show that the material was successfully prepared.

[0032] Nitrogen-doped graphene (NG) is a commercially available product purchased from Xianfeng Nanomaterial Technology Co., Ltd.

[0033] Microfluidic Chip: The schematic diagram of the microfluidic chip is shown in Figure 7 As shown, the cross-sectional view is Figure 8 As shown, it comprises: a sample inlet 1, a filter chamber 2, a microfluidic channel 3, a detection chamber 4, a sample outlet 5, an electrochemical sensor interface 6 and a filter membrane 7. The material of the chip is polydimethylsiloxane (PDMS), and the filter membrane 7 is a polyethersulfone filter membrane.

[0034] Unless otherwise specified, the conditions for each electrochemical detection of the present invention are as follows: Screen-printed carbon electrodes (Poten, Screen-printed carbon electrodes, SPCE): The substrate is PET, the working electrode is a carbon electrode (diameter 4 mm), the auxiliary electrode is a carbon electrode, and the reference electrode is silver / silver chloride; Autolab PGSTAT302N electrochemical workstation (Metrohm China Ltd.); The electrolyte was 0.1 M KCl + 5.0 mM K3[Fe(CN)6] / K4[Fe(CN)6]; Test temperature: 25℃; Cyclic voltammetry (CV): scan rate 0.02 V / s; Electrochemical impedance spectroscopy (EIS): frequency: 0.1~10 5Hz, amplitude: 0.01 V, potential: 0.2 V; Differential pulse voltammetry (DPV): potential range: -0.1~0.4V, step size: 0.005V, modulation amplitude: 0.025V, modulation time: 0.05s, interval time: 0.5s.

[0035] Example 1 1. Pt@MXene-NG Weigh 1 mg of MXene and disperse it with deionized water ultrasonically to obtain a suspension A with a concentration of 1 mg / mL. Weigh 0.5 mg of NG and disperse it with deionized water ultrasonically to obtain a suspension B with a concentration of 1 mg / mL. Combine suspension A and suspension B, stir them magnetically at room temperature for 2 h, and centrifuge them at 10,000 rpm for 3 min. Take the precipitate to obtain MXene-NG.

[0036] 200 μL of 10 mg / mL H2PtCl6 solution was transferred to an appropriate amount of deionized water, and then 3 mg of MXene-NG was added to make the volume 3 mL. After ultrasonic treatment for 30 min, 0.5 mL of 1.5 M NaBH4 solution was slowly added dropwise under magnetic stirring. After magnetic stirring for 4 h, the mixture was centrifuged at 10,000 rpm for 3 min, and repeatedly washed and centrifuged with deionized water and anhydrous ethanol to obtain Pt@MXene-NG.

[0037] from Figure 1 (B) The infrared characterization results show that when MXene is combined with NG, a wavelength of 1560 cm -1 The CN stretching vibration belonging to NG appears at , and its IR spectrum hardly changes after anchoring Pt nanoparticles (NPs) on MXene-NG.

[0038] from Figure 2 The scanning electron microscopy characterization results show that MXene-NG has obvious wrinkles and multilayer stacking, and its surface is rough and has complex textures. The reason for this may be the defects and holes generated by the composite of NG and MXene. The edges show irregular and curled morphology. These structural features can provide MXene-NG with a large effective surface area, thereby providing a large number of active sites. After anchoring Pt NPs to MXene-NG, it can be seen that Pt NPs are evenly dispersed on the layered structure and wrinkled surface of MXene-NG, forming bright dots, showing good particle dispersion and uniformity. Pt NPs are mostly spherical, and the interface between them and the matrix is ​​clearly visible, indicating that the two are closely combined.

[0039] 2. Construction of electrochemical sensor (1) Pt@MXene-NG was ultrasonically dispersed in deionized water to obtain a 2 mg / mL suspension. 20 μL of the suspension was evenly dropped onto the working electrode of SPCE and dried under an infrared lamp to obtain Pt@MXene-NG / SPCE. In addition, MXene-NG / SPCE, MXene / SPCE, and NG / SPCE were prepared under the same conditions and operations for comparison.

[0040] (2) Pt@MXene-NG / SPCE was placed in a mixed solution of 5-HT (1 mM) and o-phenylenediamine (7 mM) and subjected to cyclic voltammetry scanning (potential range: 0-0.8 V, scan rate: 0.1 V / s, step size: 0.00244 V). After scanning for 25 cycles, the sample was eluted at a constant potential (-0.4 V) for 50 s (eluent: 0.5 M HCl) to obtain MIP / Pt@MXene-NG / SPCE modified with molecular imprinting polymer (MIP). Under the same conditions, a solution of o-phenylenediamine without 5-HT was used to obtain non-imprinted NIP / Pt@MXene-NG / SPCE.

[0041] 3. Electrochemical characterization from Figure 3 (A) The DPV curves of each electrode show that the redox peaks observed on MXene / SPCE, MXene-NG / SPCE, and Pt@MXene-NG / SPCE are significantly improved compared to bare SPCE, among which the peak values ​​of SPCE are 12.392 μA, MXene / SPCE are 137.28 μA, MXene-NG / SPCE are 227.4 μA, and Pt@MXene-NG / SPCE are 344.65 μA. The peak current of MXene-NG / SPCE is significantly higher than that of MXene / SPCE, and after loading Pt NPs on its surface, the peak current of Pt@MXene-NG / SPCE is further increased, which may be due to the large specific surface area and good electrocatalytic activity of the Pt@MXene-NG composite material, which promotes the electron transfer speed and has better electrochemical performance.

[0042] from Figure 3(B) From the EIS curves of each electrode, it can be seen that the bare SPCE shows a large semicircle arc. The diameter of the arc in the high-frequency region of MXene / SPCE is significantly reduced, while the diameters of the arcs in the high-frequency regions of MXene-NG / SPCE and Pt@MXene-NG / SPCE are further reduced, and Pt@MXene-NG / SPCE has the smallest diameter. Since conductivity is inversely proportional to surface resistance, the conductivity order of each electrode is SPCE < MXene / SPCE < MXene-NG / SPCE < Pt@MXene-NG / SPCE, indicating that the Pt@MXene-NG composite increases the electron transfer kinetics and has good conductivity, thus effectively improving the electron transfer efficiency between the electrode and the target molecule. The result is consistent with the DPV result.

[0043] The CV curves of Pt@MXene-NG / SPCE in 0.1 M KCl + 0.5 mM K3[Fe(CN)6] / K4[Fe(CN)6] electrolyte were measured at different scan rates (5 to 700 mV / s) (as shown in Figure 4 (A)). According to the Randles–Sevcik equation: where I p is the peak current, n represents the number of electrons participating in the redox reaction (for K3[Fe(CN)6], n = 1), A is the electrode surface area (cm 2 ), D is the diffusion coefficient (7.6×10 -6 cm 2 s -1 ), c is the concentration of [Fe(CN)6] 3- / 4- , and v is the scan rate. Subsequently, a linear fitting plot of I p versus v 1 / 2 was plotted (as shown in Figure 4 (B)) to determine the electrochemically active surface area of Pt@MXene-NG / SPCE from its slope. The calculated electrochemically active surface area was 1.289 cm 2 . The electrochemically active surface areas of the bare SPCE, MXene / SPCE, and MXene-NG / SPCE were measured in the same way and were 0.189 cm 2 , 0.377 cm 2 , and 0.881 cm 2 , respectively. The results are consistent with the previous CV and EIS results. Modifying the electrode surface with Pt@MXene-NG greatly increases its electrochemically active surface area.

[0044] The roughness factor (fr) of the modified electrode depends on the electrode size (actual surface) and the number of redox centers available on this surface. In the formula, I p1 is the peak current of the bare SPCE, I p2 is the peak current of the modified electrode, A1 is the electrochemically active surface area of ​​bare SPCE, and A2 is the electrochemically active surface area of ​​the modified electrode. Therefore, the fr of Pt@MXene-NG / SPCE is calculated to be 6.82, and the fr of MXene / SPCE and MXene-NG / SPCE are 1.99 and 4.66, respectively.

[0045] 5-HT detection (1) MIP / Pt@MXene-NG / SPCE was incubated in 5-HT solutions with different concentrations (2000, 1500, 1000, 500, 250, 125, and 62.5 ng / mL) for 9 min, and the 5-HT that was not bound to the electrode surface was rinsed with PBS buffer solution.

[0046] (2) The electrochemical response of MIP / Pt@MXene-NG / SPCE in electrolyte was determined by DPV method.

[0047] The DPV curves of MIP / Pt@MXene-NG / SPCE after incubation in 5-HT solutions with different concentrations are shown in Figure 2. Figure 5 (A) As shown. Taking the difference in current response before and after incubation (ΔI) as an indicator, a linear fit was performed between ΔI and 5-HT concentration. The results are shown in Figure 5 As shown in (B), 5-HT has a good linear relationship with ΔI in the range of 62.5~2000 ng / mL, and the linear equation is: ΔI=26.43469lnC 5-HT -46.40067 (R 2 =0.99547), limit of detection (LOD) =25.76 ng / mL.

[0048] (V) Selectivity and stability Dopamine (DA), benzoic acid (BA), ascorbic acid (AA), SO4 2- As an interfering substance, the selectivity of the constructed sensor was investigated by measuring the DPV response of the sensor after incubation with a solution containing 1000 ng / mL of interfering substances and 500 ng / mL of 5-HT. Figure 6 (A) shown.

[0049] from Figure 6(A) It can be seen that the constructed MIP / Pt@MXene-NG / SPCE has good selectivity whether the interferent exists alone or when the interferent coexists with 5-HT.

[0050] The MIP / Pt@MXene-NG / SPCE was placed in a refrigerator at 4 °C for 10 days, and the same 5-HT solution (500 ngmL -1 ) for testing, and the test results are as follows Figure 6 As shown in (B), it can be seen that after 10 days of refrigeration, ΔI still reached 92% of that before refrigeration, and the RSD value was 0.023, indicating that the constructed sensor has good stability.

[0051] 6. Detection of serum samples (spike recovery method) Insert the MIP / Pt@MXene-NG / SPCE into the detection chamber of the microfluidic chip to construct a microfluidic electrochemical sensor for use.

[0052] Male SD rats (180-220 g) were purchased from the Experimental Animal Center of Lanzhou University (license number SCXK (Gan) 2023-0003) and were housed under standard laboratory conditions (temperature 25 ± 2 °C, relative humidity 60% ± 10%). All procedures were performed in accordance with the ethical standards of the World Medical Association and approved by the Ethics Committee of the School of Pharmacy of Lanzhou University. Blood was collected from rats by orbital bleeding and placed in a blood collection tube with anticoagulant and shaken for later use.

[0053] A certain amount of 5-HT standard was added to the rat blood with anticoagulant, and injected into the microfluidic chip using a syringe pump (injection speed of 50 μL / min). After incubation for 9 minutes, PBS buffer solution was injected to flush the channel and residual samples in the detection chamber. Finally, electrolyte was injected for DPV detection. The 5-HT content in the blood was calculated according to the linear equation of ΔI and 5-HT concentration to verify the practicality of the sensor. The results are shown in Table 1.

[0054] Table 1 MIP / Pt@MXene-NG / SPCE for detection of 5-HT in rat whole blood samples sample Spiked amount (ng / mL) <![CDATA[Measured value (ng / mL) a > RSD (%) Recovery rate (%) 1 0 365.04 1.2 - 2 400 692.45 4.3 90.49 3 800 1164.45 2.0 99.95 4 1500 1900.74 2.4 101.91 a The average value of 3 consecutive measurements The test results show that the MIP / Pt@MXene-NG / SPCE constructed in the present invention has good practicality.

[0055] Embodiment 2~5 MXene-NG was prepared with a MXene:NG mass ratio of 3:1, 2:1, 1:1, and 1:2, respectively, and the preparation operation was the same as that of MXene-NG in Example 1. MXene-NG was dispersed into a 2 mg / mL suspension using secondary water dispersion. 15 μL of the suspension was drop-coated on the SPCE working electrode to obtain MXene-NG / SPCE. The DPV response current of each MXene-NG / SPCE in the electrolyte is as follows Fig. 9 As shown in (A), it can be seen that the optimal mass ratio of MXene and NG is 2:1.

[0056] Embodiment 6~9 The preparation of Pt@MXene-NG / SPCE was the same as in Example 1, except that the volume of H2PtCl6 solution was adjusted to 100, 300, 400, and 500 μL. The DPV response current of each Pt@MXene-NG / SPCE in the electrolyte is as follows Fig. 9 As shown in (B), it can be seen that the optimal volume of H2PtCl6 solution is 200μL.

[0057] Embodiments 10 to 13 The preparation of Pt@MXene-NG / SPCE was the same as in Example 1, except that the volume of the Pt@MXene-NG suspension drop-coated on the SPCE was adjusted to 14, 16, 18, and 22 μL. The DPV response current of each Pt@MXene-NG / SPCE in the electrolyte is as follows Fig. 9 As shown in (C), it can be seen that the optimal drop volume is 20 μL.

[0058] Embodiments 14 to 16 The preparation of MIP / Pt@MXene-NG / SPCE was the same as in Example 1, except that the molar ratio of 5-HT to o-phenylenediamine during electropolymerization was adjusted to 1:5, 1:9, and 1:11, and the concentration of 5-HT was fixed at 1 mM. The difference in DPV response of each MIP / Pt@MXene-NG / SPCE in the electrolyte before and after re-incubation with 2000 ng / mL 5-HT solution is as follows Fig. 9 As shown in (D), it can be seen that the optimal molar ratio of 5-HT to o-phenylenediamine is 1:7.

[0059] Embodiments 17 to 19 The preparation of MIP / Pt@MXene-NG / SPCE was the same as in Example 1, except that the number of scanning cycles during electropolymerization was adjusted to 15, 20, and 30. The difference in DPV response of each MIP / Pt@MXene-NG / SPCE in the electrolyte before and after re-incubation with 1000 ng / mL 5-HT solution is as follows: Fig. 9As shown in (E), it can be seen that the optimal scanning number for electropolymerization is 25 cycles.

[0060] Embodiment 20-22 The preparation of MIP / Pt@MXene-NG / SPCE was the same as in Example 1, except that the elution time after electropolymerization was adjusted to 30, 70, and 100 s. The difference in DPV response of each MIP / Pt@MXene-NG / SPCE in the electrolyte before and after re-incubation with 1000 ng / mL 5-HT solution is as follows: Fig. 9 As shown in (F), it can be seen that the maximum response is achieved after elution for 70 s after electropolymerization, but visible cracks occasionally appear on the electrode surface. Therefore, the optimal elution time is set at 50 s.

[0061] Embodiments 23 to 26 The detection process of 5-HT (1000 ng / mL) was the same as in Example 1, except that the incubation time of MIP / Pt@MXene-NG / SPCE in 5-HT solution was adjusted to 1, 3, 6, and 12 min. The difference in DPV response of the sensor in the electrolyte after incubation for different time periods is as follows Fig. 9 As shown in (G), it can be seen that when the incubation time reaches 9 min, it tends to be stable, indicating that the re-adsorption of 5-HT in the molecular imprinting polymer has reached saturation, so 9 min is the optimal incubation time.

[0062] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An electrochemical sensor for detecting 5-hydroxytryptamine, the electrochemical sensor comprising an electrode, characterized in that: The surface of the electrode is modified in sequence with: (a) Composite materials consisting of two-dimensional layered transition metal carbides, nitrogen-doped graphene, and platinum nanoparticles. (b) Molecularly imprinted polymer with 5-HT as the template molecule.

2. The electrochemical sensor according to claim 1, characterized in that: The electrode is a carbon electrode, preferably a screen-printed carbon electrode.

3. The electrochemical sensor according to claim 1, characterized in that: The two-dimensional layered transition metal carbide is two-dimensional layered Ti3C2.

4. The electrochemical sensor according to claim 1, characterized in that: The mass ratio of the two-dimensional layered transition metal carbide to the nitrogen-doped graphene is 3:1 to 1:2, preferably 2:1; The ratio of the total mass of the two-dimensional layered transition metal carbide and the nitrogen-doped graphene to the mass of the platinum nanoparticles is 5:1-1:1, preferably 3:

1.

5. The electrochemical sensor according to claim 1, characterized in that: The composite material is prepared by the following steps: The two-dimensional layered transition metal carbide and nitrogen-doped graphene are mixed in a water solvent and separated to obtain MXene-NG; The composite material is obtained by mixing MXene-NG and chloroplatinic acid in a water solvent, and then adding a reducing agent to reduce the chloroplatinic acid.

6. The electrochemical sensor according to claim 1, characterized in that: The modification amount of the composite material on the electrode surface is 20-50 μg.

7. The electrochemical sensor according to claim 1, characterized in that: The monomer of the molecular imprinting polymer is o-phenylenediamine.

8. The electrochemical sensor according to claim 1 or 7, characterized in that: The molecular imprinting polymer is modified on the electrode surface by electropolymerization.

9. The electrochemical sensor according to claim 8, characterized in that: The electropolymerization method comprises the following steps: (1) placing the electrode modified with the composite material in a solution containing template molecules and polymer monomers, and performing cyclic voltammetry scanning; (2) After scanning, the template molecules are eluted; Preferably, in step (1), the potential range of the cyclic voltammetry scan is: 0-0.8 V, the scan rate is: 0.1 V / s, and the number of scans is 15-30; Preferably, step (2) adopts constant potential elution, and the eluent is a hydrochloric acid solution, and more preferably, the potential during elution is -0.4V; Preferably, the molar ratio of the template molecule to the polymer monomer is 1:5-1:11, more preferably, the molar ratio of the template molecule to the polymer monomer is 1:7, and the concentration of the polymer monomer is 7 mmol / L.

10. A method for detecting 5-hydroxytryptamine, comprising: (1) incubating the electrochemical sensor according to claim 1 in a 5-hydroxytryptamine sample solution for a certain period of time; (2) Using the DPV method to measure the electrochemical sensor before and after incubation, the current response difference before and after incubation is obtained; Preferably, an electrolyte containing K3[Fe(CN)6] / K4[Fe(CN)6] is used as the electrolyte for DPV measurement.